Thiourea-catalyzed Diels–Alder reaction of a naphthoquinone monoketal dienophile - Kramer, Carsten S.; Bräse, Stefan (Beilstein Journal of Organic Chemistry, 2013)
A variety of organocatalysts were screened for the catalysis of the naphthoquinone monoketal Diels–Alder reaction. In this study we found that Schreiner's thiourea catalyst 10 and Jacobson's thiourea catalyst 12 facilitate the cycloaddition of the sterically hindered naphthoquinone monoketal dienophile 3 with diene 4. The use of thiourea catalysis allowed for the first time the highly selective synthesis of the exo-product 2a in up to 63% yield. In this reaction a new quaternary center was built. The so formed cycloaddition product 2a represents the ABC tricycle of beticolin 0 (1) and is also a valuable model substrate for the total synthesis of related natural products.
Keywords: beticolin 0; Diels–Alder reaction; natural product; organocatalysis; thiourea catalysis; total synthesis